(untitled) (Archive of Conferences, 2021)
Organized by the Organization for Economic Co-operation and Development, the PISA International Assessment Program is a program to help determine the literacy and competency levels of students aged 15-16. It should be noted that PISA is recognized as the most prestigious and effective international research program in the world. In this article, you can learn more about the PISA program, as well as Uzbekistan’s participation in the program.